Nasakh dalam Ulumul Qur’an: Konsep, Klasifikasi, dan Relevansinya dalam Dinamika Hukum Islam - Rahayu, Siti; Putra, Alhidayah Riski; Zufriyatun, Zufriyatun (AL-FIKRA, 2023)
Nasakh dalam Ulumul Qur’an: Konsep, Klasifikasi, dan Relevansinya dalam Dinamika Hukum IslamTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//